Circular RNA MTO1 suppresses tumorigenesis of gastric carcinoma by sponging miR‐3200-5p and targeting PEBP1. (August 2020) - Hu, Kefeng; Qin, Xiaoxuan; Shao, Yongfu; Zhou, Yuping; Ye, Guoliang; Xu, Shuchang
Abstract: Gastric carcinoma (GC) is one of the most common cancers with the fifth highest incidence of malignant tumors and the second highest death rate in the world. Ever-increasing investigations have shown that circular RNAs (circRNAs) are involved in the development of numerous cancers. But so far, the recognization for circMTO1 that is realized and studied as a cancer-suppressing gene is a small part and the regulatory mechanism of circMTO1 in GC has yet to be further explored. In this study, our experimental results delineated that circMTO1 exhibited much lower expression level in GC tissues and cells. CircMTO1 overexpression slowed down GC progression via inhibiting cell proliferation, migration, invasion and epithelial‐mesenchymal transition (EMT) process. Besides, circMTO1 acted as a sponge for miR‐3200-5p as well as it could negatively regulate the expression of miR‐3200-5p. Moreover, circMTO1 was verified to compete with PEBP1 to bind to miR‐3200-5p, thus decelerating the development of GC. In a word, this study was the first to indagate the underlying mechanism of circMTO1 in GC and confirmed circMTO1 exerted its anti-cancer effects by miR‐3200-5p/PEBP1 axis, implying that circMTO1 may become a new promising therapeutic target for GC patients. Highlights: circMTO1 expression is prominently downregulated in gastric carcinoma. circMTO1 inhibits the progression of gastric cancer and serves as a sponge for miR-3200-5p. PEBP1 is the downstream target gene of miR-3200-5p. circMTO1 acts as a cancer suppressor gene in gastric carcinoma via miR-3200-5p/PEBP1 axis.